2017
DOI: 10.7717/peerj-cs.127
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating the XGBoost algorithm using GPU computing

Abstract: We present a CUDA-based implementation of a decision tree construction algorithm within the gradient boosting library XGBoost. The tree construction algorithm is executed entirely on the graphics processing unit (GPU) and shows high performance with a variety of datasets and settings, including sparse input matrices. Individual boosting iterations are parallelised, combining two approaches. An interleaved approach is used for shallow trees, switching to a more conventional radix sort-based approach for larger … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
85
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(86 citation statements)
references
References 11 publications
0
85
0
1
Order By: Relevance
“…Machine learning techniques, such as GBRTs, are considered superior in predicting when compared to statistical methods (Elith, Leathwick & Hastie, 2008). XGBoost, in particular, is regarded as the state-of-the-art tree boosting system, yielding very fast and accurate predictions (Chen & Guestrin, 2016;Mitchell & Frank, 2017). One of the main advantages of GBRTs over statistical methods is the possibility of efficiently modelling multilevel variable interactions (Elith et al, 2008).…”
Section: Predicting Growth Coefficients For Trait Combinations and mentioning
confidence: 99%
“…Machine learning techniques, such as GBRTs, are considered superior in predicting when compared to statistical methods (Elith, Leathwick & Hastie, 2008). XGBoost, in particular, is regarded as the state-of-the-art tree boosting system, yielding very fast and accurate predictions (Chen & Guestrin, 2016;Mitchell & Frank, 2017). One of the main advantages of GBRTs over statistical methods is the possibility of efficiently modelling multilevel variable interactions (Elith et al, 2008).…”
Section: Predicting Growth Coefficients For Trait Combinations and mentioning
confidence: 99%
“…XGBoost includes a regularization term that is used to alleviate overfitting, and as support for arbitrary differentiable loss functions [29]. The objective function of Xgboost consists of two parts; namely, a loss function over the training set and a regularization term that penalizes the complexity of the model as follows [30]:…”
Section: Xgboostmentioning
confidence: 99%
“…γT provides a constant penalty for each additional tree leaf, and λω 2 penalizes for extreme weights. γ and λ are user configurable parameters [30].…”
Section: Xgboostmentioning
confidence: 99%
“…CUB is a C++ template library that contains multiple algorithms for the collectives. The CUB library contains fastest [63,66] implementation for the reduction and scan collectives and is used by libraries such as Thrust [29] as well as most deep learning frameworks [5,14,23,25,68]. We compare against the latest release of CUB [62] (version 1.8) and evaluate against different parameters of the collectives.…”
Section: Optimizing Cub For Half Precisionmentioning
confidence: 99%
“…The objective of the paper is to expand the class of algorithms that can execute on TCUs-enabling the TCU to be used for non-GEMM kernels. We choose reduction and scan, since a large body of work [30,31,32,33,60,68,82,84] has shown that they are key primitives of data parallel implementations of radix sort, quicksort, string comparison, lexical analysis, stream compaction, polynomial evaluation, solving recurrence equations, and histograms. We formulate a simple mapping between reduction or scan and TCUs.…”
Section: Introductionmentioning
confidence: 99%